(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
Radioactive iodine therapy (RAIT) is an effective method of treatment for differentiated thyroid carcinomas after a total or near-total thyroidectomy. Common side effects of this therapy are nausea, sialadenitis, dry mouth, etc. Here we present an extremely rare case of black pigmentation of the tongue in a 28-year-old woman following RAIT after a total thyroidectomy due to papillary thyroid carcinoma (PTC), who presented with black discoloration of the dorsal surface of the tongue following the 3rd day of RAIT. Though the cause of discoloration remains unknown and there was a gradual reduction of dark color, a report should be done about this self-limiting, unusual side effect, which appeared to be apparently non-harmful. Bangladesh J. Nuclear Med. 26(2): 226-228, 2023